2021
DOI: 10.1038/s41467-021-24394-0
|View full text |Cite
|
Sign up to set email alerts
|

Artificial nighttime lighting impacts visual ecology links between flowers, pollinators and predators

Abstract: The nighttime environment is being altered rapidly over large areas worldwide through introduction of artificial lighting, from streetlights and other sources. This is predicted to impact the visual ecology of many organisms, affecting both their intra- and interspecific interactions. Here, we show the effects of different artificial light sources on multiple aspects of hawkmoth visual ecology, including their perception of floral signals for pollination, the potential for intraspecific sexual signalling, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 52 publications
(76 reference statements)
0
26
0
Order By: Relevance
“…Visual ecology has become a subject of increasing interest among ALAN researchers. Future studies should also explore commonly used light sources for outdoor night-time illumination at varied illuminances in relation to how artificial light at night might impact visual ecology among organism groups [274].…”
Section: Recommendations For Future Alan Research and Urban Lightingmentioning
confidence: 99%
“…Visual ecology has become a subject of increasing interest among ALAN researchers. Future studies should also explore commonly used light sources for outdoor night-time illumination at varied illuminances in relation to how artificial light at night might impact visual ecology among organism groups [274].…”
Section: Recommendations For Future Alan Research and Urban Lightingmentioning
confidence: 99%
“…Light is also used as an information source via the insect eye which can affect their visual ecology in complex ways (Land and Nilsson, 2012). Detailed modeling of spectra, intensity, reflectance and the vision of hawk-moths (Deilephila elpenor), revealed that artificial lighting can disrupt the visual ecology links between flowers, pollinators and predators (Briolat et al, 2021). Such detailed work does not exist for mosquitoes, and so the role of mosquito vision in increasing vector disease transmission is currently not well known (Gibson, 1995;Land et al, 1997;Moon et al, 2015).…”
Section: Biological Effects Of Artificial Lightmentioning
confidence: 99%
“…Whether nocturnal pollinators, such as the Heterocera, also do the same is not known. While amber LEDs and even high-pressure sodium lamps attract low numbers of insects and are less damaging compared with white broad-band LEDs with more of blue emission, a modelling study using known values of colour receptor sensitivities showed that white broad-band LEDs were more similar to moonlight in their effects on colour contrasts in the visual system of the nocturnal Deilephila elpenor (Lepidoptera: Sphingidae) (Briolat et al, 2021). Therefore, the nature of ALAN could affect Heterocera's visitation frequency at flowers of varied colours and contrast against their leaf background during nights.…”
Section: Alan and Insect Interaction Networkmentioning
confidence: 99%
“…Modelling of visual systems also revealed that the perception of colours on the wings of the Sphingidae that may be used in sexual selection or mate attraction displays or anti-predation strategies was affected by amber but not white LEDs. In an investigation of 14 species of the Sphingidae in the UK, Briolat et al (2021) found that since nocturnal moths choose settling backgrounds at night for camouflage against diurnal predators such as blue tits, colour contrast using amber LEDs would give hawkmoths inappropriate information about the colour of substrates used for resting and affect their choice of backgrounds. This mismatch between colours perceived under ALAN and those perceived under natural light available at night (moonlight and/ or starlight), can result in wrong choice of substrates, leading to greater conspicuousness and thereby greater predation risk during diurnal resting periods.…”
Section: Alan and Insect Interaction Networkmentioning
confidence: 99%